Like a rolling stone: Psychotherapy without (episodic) memory - Moore, Paul A.; Turnbull, Oliver Hugh (Frontiers in Psychiatry, 2022)
People with profound amnesia still retain the capacity to learn about the emotional value of experiences, which is crucial in developing and sustaining interpersonal relationships. In a 2017 paper, we demonstrated for the first time (with patient JL) that transferential feelings develop across the therapeutic process, despite profound episodic memory impairment after medial temporal lesions. This paper reports a second case (GA) of a profoundly amnesic patient in psychotherapy, this time after lesions to the anterior fornix. The work with GA opens issues such as the differences and similarities to the previous case, counter-transference phenomena, and the effects of hyperphagia. The findings make it clear that many phenomena are common to both GA and JL, such as forgetfulness, various types of repetition, the importance of the therapeutic alliance, and the ability to make therapeutic gain. However, there were differences between the cases, for example as regards confabulation, which may relate to either pre-morbid personality or lesion site. The paper also discusses the way in which patients of this type bear the very status of psychotherapeutic work with profoundly amnesic patients. Where others have seen barriers and in principle problems in working with such patients, we see many opportunities.